Improving Students’ Vocabulary Mastery By Using Kids’ Songs at Grade V Of SDN Pahlawan Tuanku Tambusai - Wida Rianti; Robi Elsa Putra (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aimed to improve the vocabulary mastery of fifth-grade students at SDN Pahlawan Tuanku Tambusai by using kids' songs. The background of the problem revealed that students faced difficulties in learning English vocabulary, especially in the appropriate context, spelling, and word usage. The study employed Classroom Action Research (CAR) with two cycles, where each cycle involved planning, action, observation, and reflection. The findings demonstrated that the use of kids' songs significantly enhanced students' vocabulary mastery. In the second cycle, 90.48% of the students achieved scores of ≥70, surpassing the class success criterion of 75%. In conclusion, kids' songs were effective in increasing students' motivation and vocabulary mastery..